Wholesale market + - a transformation of the wholesale market Munich in a water sensible mixed district - Enzinger,Annika (2023)
There is always talk of climate change in the future, but climate change is already present in all its facets. Intense droughts, water scarcity, severe fires, rising sea levels, floods, melting polar ice, catastrophic storms, and the decline of biodiversity are already visible. The city of Munich is no exception, as problems like heat, drought, and heavy rain increasingly have to be dealt with. We as urban designers are planning the cities of tomorrow, but climate adaptation of cities should have happened yesterday. Therefore, it is important not to wait any longer, but to adapt cities to the consequences of climate change. The wholesale market in Munich is a monofunctional area in the middle of the metropolis. It is characterized by large areas of sealed surfaces, little green infrastructure, and buildings in need of renovation. At the moment, the wholesale market area is not accessible to the public, so it is even more important to make an area in such a central location tangible for everyone. The aim is to transform this mono-functional area into a multifunctional, vibrant, sustainable district, without losing its character and identity as a wholesale market. In this process, the wholesale market is to find its place and interact with places of interaction in addition to residential, commercial, and retail buildings. To counteract climate change, elements of the bluegreen infrastructure will be implemented across the entire site. As water is a valuable resource, it is to be made tangible and visible in different ways to draw attention to it simultaneously. In the end, the goal is to bring positive climatic changes and minimize heat islands, as well as relieve the burden on sewers and avoid inner-city flooding.
Keywords: mixed use; water sensible; sustainable; transformation